Cotransport of Titanium Dioxide and Fullerene Nanoparticles in Saturated Porous Media - Cai, Li; Meiping Tong; Ma, Hanyu; Kim, Hyunjung (Environmental Science & Technology, 2013)
This study investigated the cotransport of titanium dioxide nanoparticles (nTiO(2)) and fullerene nanoparticles (nC(60)), two of the most widely utilized nanoparticles, in saturated quartz sand under a series of ionic strengths in NaCl solutions (0.1-10 mM) at both pH 5 and 7. Under all examined ionic strengths at pH 5, both breakthrough h curves and retained profiles of nTiO(2) in the copresence of nC(60) were similar to those without nC(60), indicating that nC(60) nanoparticles copresent in suspensions did not significantly affect the transport and retention of nTiO(2) in quartz sand at pH 5. In contrast, under all examined ionic strengths at pH 7, the breakthrough curves of nTiO(2) in the copresence of nC(60) in suspensions were higher and the retained profiles were lower than those without nC(60), which demonstrated that the presence of nC(60) in suspensions increased the rate of transport (decreased retention) of nTiO(2) in quartz sand at pH 7 Competition of deposition sites on quartz sand surfaces by the copresence of nC(60) was found to contribute to the increased nTiO(2) transport at pH 7. Under all examined ionic strength conditions at both pH 5 and 7, the breakthrough curves of nC(60) were reduced in the copresence of nTiO(2), and the corresponding retained profiles were higher than those without nTiO(2), indicating that the presence of nTiO(2) decreased the transport of nC(60) in quartz sand. Co-deposition of nC(60) with nTiO(2) in the form of nTiO(2)-nC(60) clusters as well as the deposition of nC(60) onto previously deposited nTiO(2) were responsible for the increased nC(60) deposition in the presence of nTiO(2) at pH 5, whereas deposition of nC(60) onto surfaces of predeposited nTiO(2) was found to be responsible for the increased nC(60) deposition at pH 7.